2000
DOI: 10.1103/physrevlett.84.3366
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Iron: The Relation between Oxidation Kinetics and Oxide Electronic Structure

Abstract: The test of the validity of the Fromhold-Cook theory of metal oxidation for the O2/Fe system in the tunnel regime is impeded by the growth of a passivating Fe2+/Fe3+ double layer at T150 degrees C, the thermionic emission of electrons is rate limiting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…The sensitivity of the XAS signal to the oxidation state and the local environment of the absorbing atom is used to follow the evolution of the oxide's structure in a quantitative and site specific manner. The use of ultrathin layers (in contrast to other studies which used thick substrates [4,5,[7][8][9]) allows one to directly resolve the intrinsic composition of the growing oxide and disentangle the influence of the substrate.The experiment was performed in situ in a compact UHV deposition chamber (base pressure 1 10 ÿ9 mbar) mounted on the A1 beam line of the DORIS III storage ring (DESY, Hamburg). The Fe K-edge absorption signal was recorded by measure of the total electron yield and fluorescence yield.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of the XAS signal to the oxidation state and the local environment of the absorbing atom is used to follow the evolution of the oxide's structure in a quantitative and site specific manner. The use of ultrathin layers (in contrast to other studies which used thick substrates [4,5,[7][8][9]) allows one to directly resolve the intrinsic composition of the growing oxide and disentangle the influence of the substrate.The experiment was performed in situ in a compact UHV deposition chamber (base pressure 1 10 ÿ9 mbar) mounted on the A1 beam line of the DORIS III storage ring (DESY, Hamburg). The Fe K-edge absorption signal was recorded by measure of the total electron yield and fluorescence yield.…”
mentioning
confidence: 99%
“…Several studies on iron oxidation at room temperature (RT) reported the possible presence of metallic Fe in the oxide layer [2,5,9], without being able to disentangle the influence of the thick Fe substrate on the origin of the signal. The use of ultrathin Fe layers allows us to address this question in a more quantitative manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, one could interpret this finding as reflecting kinetic limitations to a continued growth, presumably due to slow diffusion of either O or Ru atoms through the formed film. 37,38 While this could slow the thickening of the oxide overlayer down beyond hitherto measured time scales, it could also be that the kinetics of the on-going catalytic reaction affect the surface populations in such a way, that no further net diffusion through the film occurs and the nanometer thin oxide overlayer represents in fact a kinetically limited steady-state in the given reactive envi- ronment. This would e.g.…”
Section: Kinetically Limited Film Thicknessmentioning
confidence: 99%
“…In fact, the classic example is a slow thickening of oxide films due to limitations in the diffusion of oxygen atoms from the surface to the oxidemetal interface, or in the diffusion of metal atoms from the interface to the surface. 37,38 Directly at the surface a similar bottleneck can be the penetration of oxygen, which might be significantly facilitated at steps and defects and thus adds to their relevance particularly for the formation of surface oxides also from a kinetic point of view. Still, although such kinetic barriers might slow the oxidation process down beyond noticeable time scales, in a pure oxygen gas phase the true thermodynamic ground state will eventually be reached.…”
Section: Implications For Oxidation Catalysismentioning
confidence: 99%